Tinjauan Video Animasi Berjudul â€œLagu Anak Islami - 25 Nabiâ€ Karya Muffin Graphics Menggunakan Analisis Semiotika Saussure - Ul Haq, Edo Gavinda; Kurniawan, Ivan (Fakultas Desain Universitas Komputer Indonesia, 2021)
Animation is an audio visual media that aims to provide information on public spaces. Good animation certainly has content, images, and visual elements that support it so that the message delivered will be easily understood by the audience. Animation is also often used as a medium of education in early childhood, one of which is religious education. The company that makes animations in religious education in children is Muffin Graphics with one of its works, an animated video entitled